Pervasive human-driven decline of life on Earth points to the need for transformative change - Díaz, Sandra; Settele, Josef; Brondízio, Eduardo S; Ngo, Hien T; Agard, John; Arneth, Almut; Balvanera, Patricia; Brauman, Kate A; Butchart, Stuart H M; Chan, Kai M A; Garibaldi, Lucas A; Ichii, Kazuhito; et al. (Science (American Association for the Advancement of Science), 2019)
The human impact on life on Earth has increased sharply since the 1970s, driven by the demands of a growing population with rising average per capita income. Nature is currently supplying more materials than ever before, but this has come at the high cost of unprecedented global declines in the extent and integrity of ecosystems, distinctness of local ecological communities, abundance and number of wild species, and the number of local domesticated varieties. Such changes reduce vital benefits that people receive from nature and threaten the quality of life of future generations. Both the benefits of an expanding economy and the costs of reducing nature's benefits are unequally distributed. The fabric of life on which we all depend-nature and its contributions to people-is unravelling rapidly. Despite the severity of the threats and lack of enough progress in tackling them to date, opportunities exist to change future trajectories through transformative action. Such action must begin immediately, however, and address the root economic, social, and technological causes of nature's deterioration.